Homeopathic Medicine Improves the Motility and Vigor of Semen in Rams - Antônio Carlos Duenhas Monreal; Albert Schiaveto de Souza; Simone Marques Caramalac; Silvana Marques Caramalac; Mariana Adalgiza Gilberti Urt; Gabriel Athas; Arthur Lopes (International Journal of Veterinary Science and Research - Peertechz Publications, 2015)
The semen of rams suffers during cryopreservation, and the sperm plasma membrane breaks down during the process, creating the deleterious effect of reducing their fertilization capacity. The  homeopathic medicines Medicago sativa and Aloe vera were tested to evaluate membrane protection during cryopreservation in diluent media established for the species. Semen samples from five rams were frozen in two different diluents and analyzed after thirty days of freezing. The Glycine-Yolk-Milk diluent supplemented with Medicago sativa in the twelfth Hahnemann's centesimal potency led to decreased loss of motility and vigor of semen in rams evaluated in farms.